Protein adhesive as well as preparation method and application thereof
By adding nano-inorganic minerals and polyaziridine polymers to the protein adhesives, a polymer network structure is formed, which solves the problems of low bond strength, poor water resistance and insufficient flame retardant properties of existing protein adhesives, and improves high mechanical properties, flame retardant properties and water resistance.
Patent Information
- Application Number
- CN202411852281.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing protein adhesives are limited in the wood industry. Due to their low bonding strength, poor water resistance and insufficient flame retardant performance, they cannot meet the strength requirements of the product.
By reacting the cake isolate protein with nano-inorganic minerals, polyaziridine polymers and sulfur, a polymer network structure is formed to improve the mechanical properties, flame retardant properties and water resistance of protein adhesives.
It achieves the high mechanical properties, flame retardant properties and water resistance of protein adhesives, and meets the strength and safety requirements in the wood industry.
Smart Images

Figure BDA0005190893700000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to a protein adhesive and a preparation method and application thereof. Background Art
[0002] The wood industry uses a large amount of formaldehyde adhesives. However, formaldehyde adhesives and wood products made from them release formaldehyde and other volatile harmful substances during production and use. In order to avoid the use of formaldehyde adhesives, alternative adhesives have been sought. In recent years, protein adhesives can self-degrade under environmental conditions and will not add burden to the ecological environment. They are a natural green material. However, protein adhesives have many defects due to their protein structure. The low bonding strength and poor water resistance make them unable to meet the strength requirements of the product. The high viscosity makes it difficult to apply glue, which limits their application in the wood industry.
[0003] Therefore, it is necessary to develop a new method for preparing protein-based adhesives. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a method for preparing a protein adhesive, wherein the protein-based adhesive prepared by the method has good water resistance, good flame retardancy and good mechanical properties.
[0005] The second aspect of the present invention also provides a protein adhesive.
[0006] The third aspect of the present invention also provides an application of a protein adhesive.
[0007] According to the first aspect of the present invention, a method for preparing a protein adhesive is provided, comprising the following steps:
[0008] S1, mixing cake protein isolate, alkali and water to carry out reaction I to obtain intermediate I; mixing nano inorganic minerals, bis-(3-(triethoxysilane)propyl)-tetrasulfide and water to carry out reaction II, and performing solid-liquid separation to obtain intermediate II;
[0009] S2, mixing the intermediate I, the intermediate II, the polyethylenimine polymer and 4-dimethylaminopyridine to carry out reaction III to obtain the intermediate III;
[0010] S3, mixing the intermediate III, sulfur and a surfactant to obtain a protein adhesive.
[0011] The method for preparing the protein adhesive according to the embodiment of the present invention has at least the following beneficial effects:
[0012] The protein adhesive prepared by the method of the present invention has high mechanical properties, flame retardant properties and water resistance. The present invention first degrades the cake protein isolate to obtain intermediate I, and then modifies the nano inorganic mineral; the polyethylenimine polymer is modified on intermediate I and intermediate II, and the active group (ethylenimine group) on it reacts with sulfur to form a polymer network structure that is cross-linked between intermediate I and intermediate I, between protein and intermediate II, and between intermediate II and intermediate II. Thus, a protein adhesive with mechanical properties, flame retardant properties and water resistance can be obtained.
[0013] According to a preferred embodiment of the present invention, the nano inorganic mineral includes at least one of nano montmorillonite, nano palygorskite, nano boehmite or nano kaolin.
[0014] According to a preferred embodiment of the present invention, the cake protein isolate includes at least one of tung oil cake protein isolate, camellia oil cake protein isolate, soybean cake protein isolate, and litsea cubeba cake protein isolate.
[0015] According to a preferred embodiment of the present invention, based on the total mass of the cake protein isolate, alkali and water, the cake protein isolate accounts for 15% to 25% of the total mass.
[0016] According to a preferred embodiment of the present invention, based on the total mass of the cake protein isolate, alkali and water, the alkali accounts for 0.5% to 3% of the total mass.
[0017] According to a preferred embodiment of the present invention, the base is selected from at least one of urea, sodium hydroxide and potassium hydroxide.
[0018] According to a preferred embodiment of the present invention, based on the total mass of the nano-inorganic mineral, bis-(3-(triethoxysilane)propyl)-tetrasulfide and water, the nano-inorganic mineral accounts for 3% to 8% of the total mass.
[0019] According to a preferred embodiment of the present invention, based on the total mass of the nano inorganic mineral, bis-(3-(triethoxysilane)propyl)-tetrasulfide and water, the bis-(3-(triethoxysilane)propyl)-tetrasulfide accounts for 10% to 25% of the total mass.
[0020] According to a preferred embodiment of the present invention, the temperature of reaction II is 60-80°C.
[0021] According to a preferred embodiment of the present invention, the time of reaction II is 30 to 50 minutes.
[0022] According to a preferred embodiment of the present invention, the amount of the intermediate II is 0.5% to 2% calculated based on the total mass of the cake protein isolate, alkali and water.
[0023] According to a preferred embodiment of the present invention, the amount of the polyethylenimine polymer is 5% to 12% calculated based on the total mass of the cake protein isolate, alkali and water.
[0024] According to a preferred embodiment of the present invention, the amount of 4-dimethylaminopyridine is 0.01% to 0.5% calculated based on the total mass of the cake protein isolate, alkali and water.
[0025] According to a preferred embodiment of the present invention, the temperature of reaction III is 60-80°C.
[0026] According to a preferred embodiment of the present invention, the time of reaction III is 1 h to 2 h.
[0027] According to a preferred embodiment of the present invention, the amount of sulfur used is 1.5% to 5% calculated based on the total mass of the cake protein isolate, alkali and water.
[0028] According to a preferred embodiment of the present invention, the amount of the surfactant is 0.5% to 2% calculated based on the total mass of the cake protein isolate, alkali and water.
[0029] According to a preferred embodiment of the present invention, the surfactant is selected from at least one of sodium dodecyl sulfate, quaternary ammonium salt or sodium dodecylbenzene sulfonate, thereby promoting the dispersion of sulfur.
[0030] According to a preferred embodiment of the present invention, the particle size of the sulfur is ≤74 μm.
[0031] The second aspect of the present invention provides a protein adhesive prepared by the preparation method described in the first aspect of the present invention.
[0032] The third aspect of the present invention provides a use of the protein adhesive prepared by the preparation method described in the first aspect of the present invention in preparing a board.
[0033] According to a preferred embodiment of the present invention, the board material includes bamboo-wood composite artificial board, bamboo-wood fiberboard, particleboard, and plywood.
[0034] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0035] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0036] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0037] The raw materials in the embodiments of the present invention and the comparative examples are as follows:
[0038] Camellia oleifera cake protein, soybean cake protein isolate, nano inorganic minerals: nano montmorillonite, nano palygorskite; purchased from MacLean Reagent Network.
[0039] Bis-(3-(triethoxysilyl)propyl)-tetrasulfide, urea, sulfur, 4-dimethylaminopyridine, polyaziridine polymer, surfactant: sodium dodecyl sulfate; all of the above were purchased from Xilong Chemical and Sinopharm Chemical Reagent Co., Ltd.
[0040] Example 1
[0041] This example provides a protein adhesive, and the preparation method thereof is as follows:
[0042] S1. 20g of tea oil cake protein, 2g of urea, and 78g of water were blended and stirred for 30min until the protein was completely dissolved to obtain intermediate I; 8g of nano-montmorillonite, 20g of bis-(3-(triethoxysilane)propyl)-tetrasulfide and 72g of water were blended in proportion, stirred and reacted at 80°C for 40min. After the product was cooled, it was filtered, washed with water, and vacuum dried to obtain intermediate II.
[0043] S2. Blend 5% of intermediate II with intermediate I, add 10% of polyethylenimine polymer and 0.2% of 4-dimethylaminopyridine and continue stirring until uniform. The blended material is reacted under heating (60° C.) reflux conditions for 2 h to obtain intermediate III.
[0044] S3. Grind the sulfur through a 200-mesh sieve, add 2% sulfur and 1% sodium dodecyl sulfate into the intermediate III to obtain a protein adhesive.
[0045] Example 2
[0046] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that soybean cake protein isolate is used instead of tea oil cake protein.
[0047] Example 3
[0048] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that, based on the total mass of nano-inorganic minerals, bis-(3-(triethoxysilane)propyl)-tetrasulfide and water, bis-(3-(triethoxysilane)propyl)-tetrasulfide accounts for 10% of the total mass.
[0049] Example 4
[0050] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that the amount of the polyethylenimine polymer used is 5% based on the total mass of the cake protein isolate, alkali and water.
[0051] Example 5
[0052] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that the amount of sulfur used is 5% based on the total mass of cake protein isolate, alkali and water.
[0053] Example 6
[0054] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that nano-montmorillonite is replaced by nano-palygorskite.
[0055] Comparative Example 1
[0056] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that in step S1, nano-montmorillonite is absent.
[0057] Comparative Example 2
[0058] This example provides a protein adhesive, and the preparation method thereof is the same as that of Example 1, except that in step S1, bis-(3-(triethoxysilyl)propyl)-tetrasulfide is absent.
[0059] Comparative Example 3
[0060] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that in step S1, γ-mercaptopropyltrimethoxysilane (KH590) is used to replace bis-(3-(triethoxysilane)propyl)-tetrasulfide.
[0061] Comparative Example 4
[0062] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that in step S2, no polyethylenimine polymer is added.
[0063] Comparative Example 5
[0064] This example provides a protein adhesive, and its preparation method is the same as that of Example 1, except that sulfur is not added in step S3.
[0065] Performance Testing
[0066] The thin shavings are 6 mm thick, the raw material length is 0.8-4 mm, the aspect ratio is 15 mm, and the thickness is 0.2-0.25 mm.
[0067] The protein adhesives of the embodiments and comparative examples of the present invention were used to prepare thin bamboo wood particleboards (bamboo shavings), and the specific process was as follows: a thickness gauge of 6 mm was used, and a flat pressing method was used to prepare a board with a length, width and thickness of 600 mm × 600 mm × 6 mm for testing. Hot pressing process conditions: hot pressing temperature 125°C, hot pressing time 280s, hot pressing pressure 1.2MPa, and glue application amount 12%.
[0068] The prepared thin bamboo particleboard was tested as follows, and the results are shown in Table 1:
[0069] Internal bonding strength, static bending strength, elastic modulus, 2h water absorption thickness expansion rate, limiting oxygen index: tested according to T / CNFPIA3013-2021.
[0070] Table 1
[0071]
[0072] From the data in Table 1, it can be seen that the protein adhesives prepared in Examples 1 to 6 of the present invention have relatively high mechanical properties, water resistance and flame retardancy.
[0073] In Comparative Example 1, since no nano-montmorillonite was added, only the spontaneous hydrolysis reaction of bis-(3-(triethoxysilane)propyl)-tetrasulfide occurred in step S1, and there was no nano-montmorillonite as a substrate. Although the obtained product had a certain reactivity, the plate obtained after curing had poor mechanical properties due to the lack of support from the characteristics of nano-montmorillonite, and there was no improvement in flame retardancy.
[0074] In Comparative Example 2, bis-(3-(triethoxysilane)propyl)-tetrasulfide was not added, and the required reactive groups could not be modified on the surface of the nano-montmorillonite in step S1. The nano-montmorillonite was simply blended with the emulsion system and could not participate in the subsequent synthesis and thermal curing reaction. The reactivity of each substance was weak, and the components could not form a covalent bond, resulting in poor physical and mechanical properties. At the same time, the nano-montmorillonite was simply blended, easily aggregated and settled in the emulsion, and could not be evenly distributed inside the board, resulting in no significant improvement in flame retardancy.
[0075] In Comparative Example 3, γ-mercaptopropyltrimethoxysilane (KH590) was used to replace bis-(3-(triethoxysilane)propyl)-tetrasulfide. Although KH590 is also a silane coupling agent and can be hydrolyzed and modified on the surface of nano-montmorillonite, its structure is significantly different from bis-(3-(triethoxysilane)propyl)-tetrasulfide. Although both can modify the thiol group, the reaction activity is significantly different. After replacing with KH590, the modified nano-montmorillonite has weak reaction activity with subsequent components and cannot form an effective covalent bond connection, resulting in poor physical and mechanical properties of the board. At the same time, it also causes the components to be blended in an inhomogeneous manner, which is prone to sedimentation, resulting in concentrated and uneven distribution of nano-montmorillonite inside the board, and the flame retardant performance is not significantly improved.
[0076] In Comparative Example 4, no polyethylenimine polymer was added, and the required reactive groups could not be modified on the surface of the nano-montmorillonite in step S2, that is, it could not participate in the reaction with the sulfur monomer in step S3. The substances in S3 were simply blended, and the reaction activity was weak, and it could not be connected to itself or the protein macromolecules through covalent bonds, resulting in poor physical and mechanical properties of the formed board. At the same time, the nano-montmorillonite could not participate in the reaction in step S3, and the components were simply blended, easily aggregated and settled in the emulsion, and could not be evenly distributed inside the board, resulting in no significant improvement in flame retardancy.
[0077] No sulfur is added in Comparative Example 5. Sulfur is an important substance for the thermal curing reaction of the modified protein-based bamboo wood adhesive. The dispersion of sulfur monomer powder in the adhesive emulsion system allows the active groups on the surface of the modified nanoparticles to react with sulfur to form a stable covalent bond connection, thereby achieving the overall reaction. No sulfur is added in Comparative Example 5, so the reaction activity of each component in the final thermal curing reaction is weak, and the physical and mechanical properties of the formed board are poor. At the same time, nano-montmorillonite cannot participate in the reaction in step S3. The components are simply blended, easily aggregated and settled in the emulsion, and cannot be evenly distributed inside the board, resulting in no significant improvement in flame retardancy.
[0078] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a protein adhesive, characterized in that: The steps include: S1, mixing cake protein isolate, alkali and water to carry out reaction I to obtain intermediate I; mixing nano inorganic minerals, bis-(3-(triethoxysilane)propyl)-tetrasulfide and water to carry out reaction II, and performing solid-liquid separation to obtain intermediate II; S2, mixing the intermediate I, the intermediate II, the polyethylenimine polymer and 4-dimethylaminopyridine to carry out reaction III to obtain the intermediate III; S3, mixing the intermediate III, sulfur and a surfactant to obtain a protein adhesive.
2. The method for preparing the protein adhesive according to claim 1, characterized in that: The nano inorganic mineral includes at least one of nano montmorillonite, nano palygorskite, nano boehmite or nano kaolin.
3. The method for preparing the protein adhesive according to claim 1, characterized in that: Calculated based on the total mass of the cake and meal protein isolate, alkali and water, the cake and meal protein isolate accounts for 15% to 25% of the total mass.
4. The method for preparing the protein adhesive according to claim 1, characterized in that: Calculated based on the total mass of the nano inorganic mineral, bis-(3-(triethoxysilane)propyl)-tetrasulfide and water, the nano inorganic mineral accounts for 3% to 8% of the total mass.
5. The method for preparing the protein adhesive according to claim 1, characterized in that: The temperature of the reaction II is 60-80°C.
6. The method for preparing the protein adhesive according to claim 1, characterized in that: The amount of the intermediate II is 0.5% to 2% based on the total mass of the cake protein isolate, alkali and water; Preferably, the amount of the polyethylenimine polymer is 5% to 12% calculated based on the total mass of the cake protein isolate, alkali and water; Preferably, the amount of 4-dimethylaminopyridine used is 0.01% to 0.5% calculated based on the total mass of the cake protein isolate, alkali and water.
7. The method for preparing the protein adhesive according to claim 1, characterized in that: The temperature of the reaction III is 60-80°C.
8. The method for preparing the protein adhesive according to claim 1, characterized in that: Calculated based on the total mass of the cake protein isolate, alkali and water, the amount of sulfur used is 1.5% to 5%.
9. A protein adhesive, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the protein adhesive prepared by the preparation method according to any one of claims 1 to 8 in the preparation of boards.
Citation Information
Patent Citations
Biomass resin and preparation method of fibre oriented shaving composite board
CN105368071A
Camellia oleifera cake meal adhesive as well as preparation method and application thereof
CN110079269A
Formaldehyde-free adhesive for wood materials
CN112877011A
Two-component formaldehyde-free adhesive composition for artificial board
CN113444477A
Adhesive composition for veneer decorated plywood and veneer decorated plywood using the same
JP2001354935A